2008
DOI: 10.1016/j.amjcard.2008.02.100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soy Nuts on Adhesion Molecules and Markers of Inflammation in Hypertensive and Normotensive Postmenopausal Women

Abstract: Recently, it was shown that substituting soy nuts for nonsoy protein in a therapeutic lifestyle change (TLC) diet lowered systolic and diastolic blood pressure by 9.9% and 6.8%, respectively, in postmenopausal women with hypertension and by 5.2% and 2.9%, respectively, in normotensive postmenopausal women. In this study, to examine mechanisms for these reductions, markers of inflammation were measured, including soluble vascular cell adhesion molecule-1, soluble intercellular adhesion molecule-1, C-reactive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 10 publications
4
54
1
2
Order By: Relevance
“…When 112 volunteers at increased cardiovascular risk were randomised to a low-fat or Mediterranean diet for 3 months, significantly reduced concentrations of plasma sICAM-1 and sVCAM-1 were observed in the latter group [35]. Investigators have also reported down-regulation of these adhesion molecules following 4 week red wine [36] and 8 week soy nut interventions [37]. Such positive findings contrast with those reported here and may be related to a number of factors.…”
Section: Discussioncontrasting
confidence: 52%
“…When 112 volunteers at increased cardiovascular risk were randomised to a low-fat or Mediterranean diet for 3 months, significantly reduced concentrations of plasma sICAM-1 and sVCAM-1 were observed in the latter group [35]. Investigators have also reported down-regulation of these adhesion molecules following 4 week red wine [36] and 8 week soy nut interventions [37]. Such positive findings contrast with those reported here and may be related to a number of factors.…”
Section: Discussioncontrasting
confidence: 52%
“…Long-term intervention studies conducted using soya as a source of bioactive molecules showed reduction in levels of vascular cell adhesion molecule-1 and CRP (59,60) , but also a lack of effect on CRP (61)(62)(63) , TNFa (61,63) and IL-6 (60,62) . Increases in total isoflavones, genistein and daidzein (59) and genistein levels (63) induced by long-term soya consumption were not associated with CRP reductions (59,63) .…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 99%
“…The pathophysiological effects of OX-LDL on vascular cells have been well documented; recently, studies have reported that various components in foods can attenuate lipid oxidation [22][23][24][25] . Dietary isoflavones have been suggested to be protective against a range of diseases, including cardiovascular diseases, osteoporosis, and cancer, and have also been reported to alleviate menopausal symptoms in postmenopausal women [26][27][28] . Isoflavones (members of the class of flavonoids) belong to a group of plant compounds called phytoestrogens.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflavones are also an important class of phytoestrogens, which are found at extremely high levels in soy. Recently, the isoflavones daidzein and genistein have been shown to have beneficial physiological effects on cardiovascular disease, blood pressure and angiogenesis [8][9][10][11][12] . More recently, however, attention has shifted to isoflavone metabolites.…”
Section: Introductionmentioning
confidence: 99%